Feedback frequency of graphical countdown timers affects pedestrian estimated waiting time at red lights. (July 2022) - Cui, Zixin; Zhuang, Xiangling; Chen, Wenxiang; Ma, Guojie
Highlights: Pedestrians estimated waiting time at red phase in simulated road-crossing tasks. Feedback frequency of graphical countdown timers was manipulated. Perceived duration was shorter than actual duration. Lower feedback frequency in countdown timers led to shorter estimated duration. Arousal level and internal timer speed were not affected by feedback frequency. Abstract: Graphical countdown timers (similar to a progress bar) have the potential to shorten pedestrians' perceived waiting time at the red light. Based on the findings from human-computer interaction (HCI) and time estimation theories, the potential may be affected by feedback frequency. This study tested how the feedback frequency of countdown progress bar in traffic light influenced time estimation in a field experiment, and further explored its mechanism in a laboratory experiment. In both experiments, participants estimated various durations (30 s, 45 s, 60 s) under three levels of feedback frequency: low (0.5 Hz), medium (1 Hz), and high (2 Hz). The results showed that although waiting time was underestimated in all conditions, lower feedback frequency led to shorter estimated duration, with slight changes in different contexts. In the traffic context, the effect of feedback frequency was comparable across different countdown duration, but it became stronger at longer countdown duration in the non-traffic context. Overall, the effect of feedback frequency was accompanied by changes in neither arousal level (measured by the subjective scale and physiological indices) nor internal clock speed, which are two critical determinants of time perception. The findings have practical implications on the display design of red light and theoretical implications on time estimation processes.